Macroeconomic Adjustment and Reform in Planned Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper examines the relationship between macroeconomic stabilization and market-oriented reform in planned economies. It emphasizes that market-oriented reform should enhance the likelihood that adjustment to exogenous disturbances will involve genuine adjustment in the sense of actually eliminating or at least reducing both internal and external imbalances. Market-oriented reform should also increase the ability of the authorities to carry out stabilization policies relying on indirect rather than direct instruments. The paper argues that the sustainability of such reform may critically depend on the pursuit of policies that contain inflationary pressures, but that the environment for adoption of such policies will depend in turn on the appropriate sequencing of reform measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet